Cannabis Sativa: an integrative review of legal, toxicological and pharmacotherapeutic aspects (Research, Society and Development, 2021)
Currently, with the growing number of studies involving phytocompounds with numerous pharmacological applications, cannabis has taken a leading role in the treatment of numerous pathologies. In this context, delta 9-tetrahydrocannabinol (Δ9 -THC), cannabidiol (CBD), and cannabinol (CBN), present mainly in the Cannabis genus, have gained greater scientific focus as a natural source of these compounds, which, compared to other pharmacological substances, have fewer adverse effects. The search for evidence was conducted in the Medline, PubMed, Scielo, and LILACS databases. Forty-one articles that met the inclusion and quality criteria were selected. It was observed that the scientific literature presents strong evidence for the use of these substances in the treatment of nausea and vomiting associated with chemotherapy, analgesia in chronic pain, anorexia associated with Acquired Immune Deficiency Syndrome (AIDS), neuropathic pain and some neurological diseases such as multiple sclerosis, anxiety, insomnia, epilepsy, and in Parkinson's disease. It is concluded that the use of phytocannabinoids presented a safe toxicological profile for use in both children and adults, not being related to the development of considerable secondary problems or dependence, and their applicability in pharmaceutical formulations in the industrial area is increasing.